Insight into the Mechanism of the Michael Reaction. Issue 13 (18th April 2016) - Giraldo, Carolina; Gómez, Sara; Weinhold, Frank; Restrepo, Albeiro
Abstract: The mechanism for the nucleophilic addition step of the Michael reaction between methanethiol as a model Michael donor and several α‐substituted methyl acrylates (X=F, Cl, Me, H, CN, NO2 ) as model Michael acceptors is described in detail. We suggest a novel way to condense electrophilic Fukui functions at specific atoms in terms of the contributions from the atomic orbitals to the LUMO or, more generally, to the orbital controlling the reaction. This procedure correctly associates activation energies to local electrophilic Fukui indices for the cases treated in this work. The calculated reaction barriers strongly depend on the nature of the substituent. As a general rule, activation energies are governed by structural changes, although electronic factors are significant for electron‐withdrawing groups. Nucleophilic addition to Michael receptors is best described as a highly nonsynchronous process, in which the geometry of the transition state comprises a nonplanar six‐membered ring. Formation of the S⋅⋅⋅ C bond, which defines the interaction between the reactants, progresses ahead of all other primitive processes in the early stages of the transformation. In view of our results, we postulate that highly complex chemical reactions, as is the case for the nucleophilic addition step studied herein, that involve cleavage/formation of a total of six bonds, lower their activation energies by favoring nonsynchronicity, that is, for these types of systems, primitive changes should advance at different rates. Abstract : Be like Mike : The mechanism for the nucleophilic addition step of the Michael reaction between methanethiol as a model Michael donor and several α‐substituted methyl acrylates (X=F, Cl, Me, H, CN, NO2 ) as model Michael acceptors is described in detail. In view of our results, we postulate that the activation energy is lowered through nonsynchronicity; thus, primitive changes should advance at different rates.